2015
DOI: 10.1589/jpts.27.1701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feedback on activation of the quadriceps during weight-bearing tasks of the Wii

Abstract: [Purpose] This investigation evaluated the effect of real-time feedback on electrical activation of the quadriceps during 3 weight-bearing tasks of the Wii Fit Plus®. [Subjects] Thirty male healthy volunteers were recruited. [Methods] Activation of the vastus medialis, vastus lateralis, and rectus femoris muscles was recorded during virtual lunge, single leg extension, and single leg reach exercises. Each exercise was performed twice in 3 randomized experimental conditions (with visual feedback, with auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…Further, Da Silva et al reported low activation (relative to the maximum voluntary contraction) of the quadriceps during Wii games, which is in line with the low activations we found for the Wii games 42 .…”
Section: Discussionsupporting
confidence: 90%
“…Further, Da Silva et al reported low activation (relative to the maximum voluntary contraction) of the quadriceps during Wii games, which is in line with the low activations we found for the Wii games 42 .…”
Section: Discussionsupporting
confidence: 90%